Police consent decrees and section 1983 civil rights litigation - Powell, Zachary A. (Criminology & public policy, 2017)
Section 14141 of the Violent Crime Control and Law Enforcement Act of 1994 granted the U.S. Department of Justice (DOJ) the authority to investigate, intervene into, and force reforms within any police department deemed to exhibit a pattern or practice of police misconduct. The DOJ's primary enforcement mechanism is to sue the offending jurisdiction. Such lawsuits are typically settled with “consent decrees” or court‐ordered legal agreements to implement specified reforms. We assembled a panel data set to explore the relationship between consent decrees and civil rights litigation in 23 targeted jurisdictions. The results suggest that DOJ intervention may be associated with modest reductions in the risk of civil rights filings.